Station versus circuit training - Staley, C. I.
To most bodybuilders and fitness enthusiasts, "circuit training" is thought of as a method of integrating resistance and aerobic exercise by performing several (9-12) exercises in "vertical" progression (meaning that one performs one set of each exercise until all have been completed, as opposed to finishing all sets of the first exercise before progressing to the second) with little or no rest between exercises. The supposed (and unproven) benefit of this type of high density (work to rest ratio) exercise is that the exerciser will improve aerobic and anaerobic functioning at the same time. Unfortunately, this narrow definition has done a disservice to circuit training, and to those who have dismissed this method as an ineffective fringe variant used only by the profoundly unfit as a way of regaining some semblance of fitness. In truth, circuit training has much to offer, even for the advanced, if you'll allow for a slightly broader definition of the term, and a bit of creative application.